2020
DOI: 10.3390/f11030325
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Mitigate Nitrogen Leaching under Poplar Seedlings

Abstract: The leaching of soil nitrogen (N) has become one of the most concerning environmental threats to ecosystems. Arbuscular mycorrhizal (AM) fungi have important ecological functions, however, their influence on soil N leaching and the mechanism of action remain unclear. We conducted a two-factor (N application level × AM inoculation) experiment on poplar, and for the first time, comprehensively analyzed the mechanism by which AM fungi influence soil N leaching. The results showed that, under optimum (7.5 mM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…The highest CEC value found at the highest dosage (45 Mg ha −1 of manure) could be reduced leaching, and there were more exchangeable cations such as Na + , Ca 2+ , Mg 2+ , and K + incorporated by soil organic matter and manure itself. Similar findings on changes in soil CEC with AMF and manure are also reported by Fang et al [44] and Shi et al [43], respectively.…”
Section: Cation Exchange Capacitysupporting
confidence: 89%
“…The highest CEC value found at the highest dosage (45 Mg ha −1 of manure) could be reduced leaching, and there were more exchangeable cations such as Na + , Ca 2+ , Mg 2+ , and K + incorporated by soil organic matter and manure itself. Similar findings on changes in soil CEC with AMF and manure are also reported by Fang et al [44] and Shi et al [43], respectively.…”
Section: Cation Exchange Capacitysupporting
confidence: 89%
“…Gikas et al (2016) obtained a similar result in poplar intercropping systems. The mobile ability of NH4+N is lower than that of NO3N and NO2N; thus, the root system interception effect possibly plays a dominant role in the 20–40 cm soil layer (Fang et al, 2020; Thorup‐Kristensen et al, 2009). Therefore, root direct absorption is the main mechanism for inorganic nitrogen reduction in the upper soil layers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that AM fungus inoculation can boost plant root activity, which is a comprehensive indication of root nutrient absorption [46]. Furthermore, due to their large mycelia, which effect soil aggregation and absorb nutrients from the soil, AM fungus have been found to enhance soil quality [47]. As pointed out by studies, inoculation with AMF boosts dry matter build up, water moisture and nutrient absorption, hence boosting plant tolerance to stressors such as drought [48].…”
Section: Fungi Inoculation and Its Effects On Oil Palmsmentioning
confidence: 99%